INTELLECTUAL PROPERTY : - Parr, Russell L., author 453141; Caire, Yuridia, author 642027 (Hoboken, New Jersey : Wiley)
Stay informed about the latest developments in US intellectual property law In the latest 2021 Cumulative Supplement to the fifth edition of Intellectual Property: Valuation, Exploitation, and Infringement Damages, readers will find reliable guidance and expert commentary on the latest legislative amendments, the most recent regulatory changes, and the most impactful cases adjudicated in 2020 and 2021 in the US. You'll explore of-the-moment updates covering critical issues in the valuation, exploitation and infringement of intellectual property written by the expert team behind the celebrated text, Intellectual Property: Valuation, Exploitation, and Infringement Damages.